Assessing effectiveness of caribou management systems: Alaska's Western Arctic Herd and Canada's Beverly and Qamanirjuaq Herds - Klein, D.R.; Kruse, J.A. (Rangifer, 1996)
Our hope is that this analysis will highlight the best elements of each management system, which collectively will serve as a model to improve the management of large caribou herds in North America.